STYLE OF SCIENTIFIC THINKING IN EPOCH OF INFORMATION - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the problem of forming a neu style in scientific thinking in development in the information society.